PENYULUHAN JUMANTIK DI DUSUN PLOSO I, KARANGTRITIS, DAN KLAYU II, DESA SUMBERWUNGU - Indra Putra, Ichsan; Yunus, Ramjan; Kurnia, Bidayatul Izzah; Thiago, Fahriz (Universitas Ahmad Dahlan, Yogyakarta, 2019)
Population growth in Indonesia is increasing nowadays. Increasing in population can lead to increasing demand for home and can caused the reduction of green open space. The reduced open green space will increase the population of house mosquitoes. Today's mosquitoes are not assumed to only able to live in a dirty water, but also can live in a clean water. Therefore, regular monitoring of mosquito larvae is very important. One of the effort that can be done in regular monitoring of mosquito larvae is by forming JUMANTIK. The purpose of this activity is to form a young JUMANTIK cadre and to instill a healthy and clean lifestyle for children from an early age. This activity was carried out by presenting and practicing larvae monitoring for children in 3 hamlets, Ploso I, Karangtritis, and Klayu II. Activities in Poso I were conducted on 18th February 2019, Karangtritis on 26th January 2019, while Klayu II on 1st and 2nd February 2019. The materials that provided are DBD and the importance of JUMANTIK. The practice was carried out by direct monitoring of the surrounding water reservoirs. Counseling was done 1x with an allocation of time 30 minutes, while for the practice the allocation of time was around 90 minutes. At the end of the activities, the young JUMANTIK cadres in 3 hamlets was formed. The conclusion of this activity was that the establishment of JUMANTIK is very important and engrafting a healthy and clean lifestyle is highly recommended from an early age.